2021
DOI: 10.3390/life11030207
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Anxiolytic and Antidepressant-Like Proprieties of Carum carvi L. and Their Association with Its Antioxidant Activity

Abstract: Depression and anxiety are widespread illnesses whose consequences on patients' social and professional lives are becoming ever more dangerous and severe. The study's objective is to explore the antidepressant-like and anxiolytic activity of the polyphenolic extract of Carum carvi L. as well as its antioxidant power as they were recently associated. The predictive antidepressant activity was evaluated using the forced swimming and tail suspension test in mice, a preclinical behavioral model widely used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…Likewise, the number of tiles traversed during the open-field test increased significantly at the lowest dose used in this study. These results are in accordance with other studies using OFT to investigate the anxiolysis effect of plants and other drugs [26].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Likewise, the number of tiles traversed during the open-field test increased significantly at the lowest dose used in this study. These results are in accordance with other studies using OFT to investigate the anxiolysis effect of plants and other drugs [26].…”
Section: Discussionsupporting
confidence: 93%
“…Clinical and pre-clinical trials have reported successful use of medications for certain plant metabolites, such as alkaloids, terpenes, flavonoids, and sterols and others [ 24 , 25 ]. Medicinal plants have also proven efficacy against depression and anxiety, reported with the use of multiple plants, such as Carum carvi polyphenols at doses of 50 and 100 mg/kg [ 26 ], Coriandrum sativum at doses of 50, 100, and 200 mg/kg [ 27 ], Origanum majorana polyphenols at doses of 50 and 100 mg/kg [ 28 ], and Petroselinum sativum at doses of 50 and 100 mg/kg [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peran antioksidan sebagai antidepresan mengacu pada salah satu fungsinya dalam mencegah reaksi oksidasi, termasuk stres oksidatif (Es-safi et al, 2021). Aktivitas antioksidan pada ekstrak pucuk mangga yang sangat kuat, menjadikan ektrak ini berpotensi dangat baik dalam mekanisme pemulihan tubuh dari stres sebagai produk antidepresan alternatif.…”
Section: Skrining Fitokimia Dan Aktivitas Antioksidan Ekstrak Pucuk M...unclassified